Remodeling the Host Environment: Modulation of the Gastric Epithelium by the Helicobacter pylori vacuolating toxin (VacA) - Ik-Jung eKim; Steven R. Blanke (Frontiers in Cellular and Infection Microbiology, 2012)
Virulence mechanisms underlying Helicobacter pylori persistence and disease remain poorly understood, in part, because disease risk is multifactorial and complex. Among the bacterial factors that contribute to the cumulative pathophysiology associated with H. pylori infections, the vacuolating cytotoxin (VacA) is one of the most important. Analogous to a number of H. pylori genes, the vacA gene exhibits allelic mosaicism, with several alleles clearly associated with more severe disease. VacA is secreted by Helicobacter pylori as an intracellular-acting exotoxin. However, VacA does not fit the current prototype of AB intracellular-acting bacterial toxins, which elaborate modulatory effects through the action of an enzymatic domain translocated inside host cells. Rather, VacA may represent an alternative prototype of AB intracellular acting toxins that modulate membrane-regulated homeostasis by forming ion-conducting intracellular membrane channels. Although VacA seems to form channels in several different membranes, one of the most important target sites is the mitochondrial inner membrane. VacA subverts intracellular trafficking to mitochondria, where the toxin depolarizes the inner membrane to disrupt mitochondrial dynamics and cellular energy homeostasis as a mechanism for engaging the apoptotic machinery within host cells.